Food, Farming and Religion - Van Wieren, Gretel, author.
1 online resource
Keywords: "Although the religious and ethical consideration of food and eating is not a new phenomenon, the debate about food and eating today is distinctly different from most of what has preceded it in the history of Western culture. Yet the field of environmental ethics, especially religious approaches to environmental ethics, has been slow to see food and agriculture as topics worthy of analysis.This book examines how religious traditions and communities in the United States and beyond are responding to critical environmental ethical issues posed by the global food system. In particular, it looks at the responses that have developed within Jewish, Christian, and Muslim traditions, and shows how they relate to arguments and approaches in the broader study of food and environmental ethics. It considers topics such as land degradation and restoration, genetically modified organisms and seed consolidation, animal welfare, water use, access, pollution, and climate, and weaves consideration of human wellbeing and justice throughout. In doing so, Gretel Van Wieren proposes a model for conceptualizing agricultural and food practices in sacred terms.This book will appeal to a wide and interdisciplinary audience including those interested in environment and sustainability, food studies, ethics, and religion. "--Provided by publisher.